Economic optimization of dynamic systems using Stella®:Optimal production schedule in salmon culture. - Zúñiga, Sergio (2008)
The present article develops a number of classical economic-financial applications in continuous time based on the software Stella (Isee Systems, Inc.). The problems under analysis basically deal with modeling projected free cash flows and investments, and their Net Present Value estimation, a process which in many cases may require numerical integration. The document shows how Stella allows construction of a model in a simple fashion, and with it to make simulations that give graphical solutions, as is the case of the decision of the optimal harvest time, or the selection between alternative projects, among others.